PENGARUH BIAYA PROMOSI TERHADAP VOLUME PENJUALAN PADA PT.INDOFOOD MAKMUR TBK - gautama siregar, budi (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2017)
Adequate promotional costs are expected to help companies market their products. The principle of promotional activities is not solely to introduce products but includes efforts to maintain the stability of the sales volume of a company's products from the threat of entry of competitors to innovation and promotion and to increase sales turnover. Promotional costs at PT Indofood Makmur Tbk in 2014 to 2015 have increased but sales volume has decreased. This study has a problem statement, namely whether there is an effect of promotional costs on sales volume. This study aims to determine the effect of promotional costs on sales volume at PT Indofood Makmur Tbk for the period 2008 to 2015. Overall the results of this study indicate that promotion costs have a very strong relationship in influencing sales volume, this is evident from the results of the R2 value formed by 0.840. This means that promotion costs can affect sales volume by 84%, while the remaining 16% is influenced by other variables not included in this study. The regression test results obtained that promotion costs have a significant influence on sales volume which is indicated by the value of tcount t table, which is 12,358 1,692.